Disturbance Observer-Based Integral Sliding-Mode Control for Systems With Mismatched Disturbances - Zhang, Jinhui; Liu, Xinwei; Xia, Yuanqing; Zuo, Zhiqiang; Wang, Yijing (IEEE transactions on industrial electronics (1982), 2016)
This paper develops the disturbance observer-based integral sliding-mode control approach for continuous-time linear systems with mismatched disturbances or uncertainties. The disturbance observer is proposed to generate the disturbance estimate, which can be incorporated in the controller to counteract the disturbance. With the help of the proposed disturbance observer, both the memoryless and memory-based integral sliding surfaces and integral sliding-mode controllers are developed, respectively, and two approaches, i.e., H ∞ control and steady-state output-based approaches, are proposed to design the controller and disturbance rejection gains. Finally, the effectiveness and applicability of the proposed technique are illustrated by a numerical example and a real-time experiment.